CERES-maize predictions of maize phenology under nitrogenstressed conditions in Nigeria - Gungula, D.T.; Kling, J.; Togun, A. (Wiley, 2003)
Simulation models have the potential of greatly enhancing decision-making by farmers and researchers in Nigeria. These models however, need to be adapted before use. This study was conducted to test the phenology module of CERES-Maize model version 3.5 under varying N rates as a step toward adapting the model in the Southern Guinea Savanna of Nigeria. Data on seven late-maturing cultivars of maize (Zea mays L.) grown under 0, 30, 60, 90, and 120 kg N ha−1 in the field for two seasons were used for running the model. There was a linear relationship between N rates and days to silking and maturity with R 2 values of > 0.70 for most of the cultivars, indicating that N strongly influenced phenology. Predictions of days to silking at high N rates (90 and 120 kg N ha−1) were close, with most prediction errors of <2 d. The highest deviations in the calibration results were 4 and 2 d for 90 and 120 kg N ha−1, respectively, while in the validation results, they were 1 and 2 d. Similarly, days to maturity were closely predicted by the model at high N rates with <2-d deviations for most predictions. At low N rates, however, there were greater deviations in model predictions. This shows that the CERES-Maize model can be reliably used for predicting maize phenology only under nonlimiting N conditions. Thus, a N stress factor needs to be incorporated into the model for more accurate phenology prediction in low-N tropical soils.